Pengaruh Kesehatan dan Pekerjaan Terhadap Kepuasan hidup pada Lansia di Posyandu Lansia Kelurahan Balowerti Kota Kediri - Sucipto Sucipto; Fajar Rinawati (Akademi Keperawatan Dharma Husada Kediri, 2017)
Everyone person wants a happy life, including elderly people. Every measurement will be taken into action to achieve that goal. A happy feeling will help elderly people to connect and interact with others. However, not all elderly people feel happy in their age. Some elderly experience sadness and disappointment due to declining health and job loss. This research aims at analysing the influence of health and employment on elderly life satisfaction at Posyandu Lansia, Balowerti Village, District of Kediri. This study employed analytical approach with cross sectional data collection. The statistical test used in this study was linier regression, with p value = 0.00. The result shows health as having more influence towards life satisfaction of elderly people compare the employment. Elderly people’s mental change, self-concept change, and unprepraredness affected from illness lead to the feeling of being useless and becoming the burden of the family. This feelings affect elderly people’s life satisfaction. Support from family and society is necessary for elderly people to adapt with their illness. Keyword: elderly people, satisfaction, health, employment